Variables Affecting Extreme Poverty of Agricultural Sector Households in Indonesia - Syafira Karunia Sari; Nucke Widowati Kusumo Projo (Universitas Negeri Malang, 2025)
This research aims to describe the characteristics of households and the variables that influence extreme poverty in agricultural sector households in Indonesia.This research used the Socio-Economic Survey 2022 with descriptive analysis and binary logistic regression. The results show that 20.78 percent of agricultural sector households are extremely poor. The characteristics of an extremely poor household are: the average number of household members is 5-6 people, the household head is male, the household head is of productive age, lives in a rural area, the maximum education level of the household member is junior high school/equivalent, more than half of the household members have health insurance, and experience food insecurity, does not own their residence, no assets, no credit, not receivingnon-cash government assistance, receivingFamily Hope Program, the proportion of household members working is a maximum of 0.5, sanitation condition are poor, and no electricity available. Variables that influence the status of extremely poor households are the number of household members, age of household heads, classification of area of residence, food insecurity, asset ownership, credit ownership, Family Hope Program, housing ownership, proportion of household members working, sanitation condition, and availability of electricity.